Era Revolusi Industri 4.0 Sebagai Peluang dan Tantangan Pelaku UMKM - Sheila Silvia Permatasari; Endyastuti Pravitasari; Yanuar Rahmadan; Kiko Armenita Julito (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2023)
The implementation of community service activities facilitated by Dinas Koperasi dan UMKM Garut has the main goal of preparing the community to face the onslaught of technology that continues to develop in this digital era. The implementation of community service activities is carried out using the workshop method which is divided into three sessions with different materials. The session on the industrial revolution 4.0 was held in the first session with the speaker from the University of 17 August 1945 Jakarta lecturer. This service activity is expected to help MSME to keep abreast of digital technology developments, especially after Covid-19, the level of community dependence on technology is getting higher. This of course can be a huge opportunity for MSME if they can master the use of technology. One of the findings obtained from this workshop activity is that MSME are still unfamiliar with several technologies that are supposed to assist their activities. This makes their activities can not be carried out optimally. Therefore, this workshop activity is expected to be able to help the business activities of MSME by starting to use some of the existing technology.